1991
DOI: 10.1104/pp.97.1.188
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water and Temperature Stress on the Temperature Dependence of the Reappearance of Variable Fluorescence following Illumination

Abstract: The temperature dependence of the rate and magnitude of the reappearance of photosystem 11 (PSII) variable fluorescence following illumination has been used to determine plant temperature optima. The present study was designed to determine the effect of a plant's environmental history on the thermal dependency of the reappearance of PSII variable fluorescence. In eter, the Michaelis constant (Kin), to define the limits of thermal stress (2, 8, 10, 11). These measures are used as indicators of metabolic effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…Similar differences in gas exchange patterns during leaf development have been reported for numerous species (Choinski and Johnson, 1993;Choinski and Wise, 1998;Woodall et al, 1998;Choinski et al, 2003) in which juvenile, not fully expanded leaves had lower conductance and photosynthetic rates than mature leaves, on an equal leaf area basis. Although many studies have reported leaf temperature data on mature leaves under field conditions (Ansari and Loomis, 1959;Ferguson and Burke, 1991;Singsaas and Sharkey, 1998;Wise et al, 2004), this is the first report that shows leaf temperature data in both juvenile and mature leaves on the same plant in conjunction with anatomical data on stomatal development.…”
Section: Discussionmentioning
confidence: 89%
“…Similar differences in gas exchange patterns during leaf development have been reported for numerous species (Choinski and Johnson, 1993;Choinski and Wise, 1998;Woodall et al, 1998;Choinski et al, 2003) in which juvenile, not fully expanded leaves had lower conductance and photosynthetic rates than mature leaves, on an equal leaf area basis. Although many studies have reported leaf temperature data on mature leaves under field conditions (Ansari and Loomis, 1959;Ferguson and Burke, 1991;Singsaas and Sharkey, 1998;Wise et al, 2004), this is the first report that shows leaf temperature data in both juvenile and mature leaves on the same plant in conjunction with anatomical data on stomatal development.…”
Section: Discussionmentioning
confidence: 89%
“…A strong correlation between the temperatures delimiting the TKWs of wheat, cotton, bell pepper, and petunia and the thermal dependence of the reappearance of the variable component of PSII fluorescence in the dark following illumination has been reported previously (Burke, 1990;Ferguson et al, 1991). Because of the difference in TKW between that determined for NADH-hydroxypyruvate reductase in the present study and that reported previously for NADPHglutathione reductase (Mahan et al, 1990), we have used the fluorescence technique to further establish the bounds of the temperature optimum of cucumber.…”
Section: Fluorescence Analysesmentioning
confidence: 95%
“…Comparison of the thermal response of PSII fluorescence reappearance with the temperature sensitivity of the apparent K, of hydroxypyruvate reductase for NADH showed that temperatures providing maximal fluorescence reappearance corresponded with temperatures providing the minimum apparent K, , , values (Burke, 1990;Ferguson et al, 1991). The fluorescence technique not only provided a useful tool for the analysis of plant temperature optima, but also strengthened the TKW concept.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of the thermal kinetic window was to provide a general indicator of the range of temperatures in which the optimal temperature for metabolism was located. The best correlative evidence of the validity of the TKWs comes from the determination of the temperature dependence of the reappearance of photosystem II variable fluorescence following illumination [4] [5]. The chlorophyll fluorescence functions as a natural indicator of the in vivo temperature characteristics of the plant.…”
Section: Introductionmentioning
confidence: 99%